Cash disbursement procedure in terms of liability and payment of ACI Godrej Agrovet Private Limited - Hoque, Syeda Tasnima (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.